Behaviour modelling of passive intermodulation in a complex non‐linear system - Junyu Luo; Jinchun Gao; Lingyu Bi; Ziren Wang; Xiaolong Xu; Yilin Zhou; Gang Xie (IET Microwaves, Antennas & Propagation, 2023)
Abstract A novel method for modelling the passive intermodulation (PIM) in radio frequency (RF) devices, which works as a complex non‐linear system, was proposed. Both behaviour modelling and experimental validation were introduced to clarify the generation of PIM in a parallel and series non‐linear system. Taking the coaxial connector as an example, two types of N‐type connectors with 4 and 6 contact petals were selected and put into research. The measurements both agree well with the predicted results, validating the proposed model.